Posisi Pendidikan Agama Islam dalam Menghadapi Problematika Masyarakat Modern - Alhanin, Azzy; Al Fitri, M. Faza; S, Hefik Nadzif Ulfiyah; Haminati, Arini (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The aim of this article is to investigate the role and relevance of Islamic religious education in facing the complexity of modern society and to explore PAI implementation strategies in overcoming the problems faced by the millennial generation. The research method used is a qualitative approach with library methods to collect data from various primary and secondary sources. The results of the analysis show that Islamic religious education has an important role in shaping the character and morals of the younger generation and preparing them to face the challenges of contemporary society. Effective implementation of PAI involves the choice of relevant material, an inclusive approach, the use of technology in learning, and strengthening student character. In conclusion, Islamic religious education must continue to adapt to the times and become a relevant solution in forming individuals who are faithful, devout and have noble character in an increasingly complex modern society.